2021
DOI: 10.3389/fcell.2021.619329
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of CircRNAs in Regulating Muscle Development of Livestock Animals

Abstract: The muscle growth and development of livestock animals is a complex, multistage process, which is regulated by many factors, especially the genes related to muscle development. In recent years, it has been reported frequently that circular RNAs (circRNAs) are involved widely in cell proliferation, cell differentiation, and body development (including muscle development). However, the research on circRNAs in muscle growth and development of livestock animals is still in its infancy. In this paper, we briefly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 101 publications
0
8
0
Order By: Relevance
“…15 To date, numbered circRNAs have been identified and reported to regulate cell biological processes in skeletal muscle as a novel regulator of muscle development. 16 For example, circT-MTC1 inhibits skeletal muscle satellite cell differentiation by sponging miR-128-3p, 9 while circFGFR4 sponged miR-107 promotes cell differentiation in primary myoblasts by targeting Wnt3a, 17 and circEch1 induces myoblast differentiation and skeletal muscle regeneration. 7 Nonetheless, the precise function and underlying molecular mechanisms of circRNAs in the myogenesis and development of goat skeletal muscles remain largely unknown.…”
mentioning
confidence: 99%
“…15 To date, numbered circRNAs have been identified and reported to regulate cell biological processes in skeletal muscle as a novel regulator of muscle development. 16 For example, circT-MTC1 inhibits skeletal muscle satellite cell differentiation by sponging miR-128-3p, 9 while circFGFR4 sponged miR-107 promotes cell differentiation in primary myoblasts by targeting Wnt3a, 17 and circEch1 induces myoblast differentiation and skeletal muscle regeneration. 7 Nonetheless, the precise function and underlying molecular mechanisms of circRNAs in the myogenesis and development of goat skeletal muscles remain largely unknown.…”
mentioning
confidence: 99%
“…However, the transformation mechanism of the LT muscle fiber types by ceRNAs and its influence on meat quality in Tibetan sheep at different growth stages remains unclear. There were a lot of studies that have described circRNA in humans (17,21), animals (22,23), plants (24,25), and microorganisms ( 26) using an RNA-Sequencing approach. Yan et al (27) have identified a total of 5,177 circRNAs in the longissimus dorsi muscle of the Kazakh cattle and Xinjiang cattle, and have found the process of muscle development was related to the differentially expressed circRNAs (DE circRNAs).…”
Section: Introductionmentioning
confidence: 99%
“…The chromosome-wise distribution of circRNAs showed that most of the circRNAs originated from chromosome 2 (227), followed by chromosomes 3 (160) and 4 (155) ( Figure 4B ). circRNAs have multiple regulatory roles which can enrich breeding and improve economic traits related to buffalo ( Fu et al, 2018 ; He et al, 2021 ; Yang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The miRNAs could be used to find their lncRNAs target; action of miRNAs on lncRNAs could be sequestering them by binding or destroying them by cleaving ( Assmann et al, 2019 ; Xie et al, 2020 ). The tissue-wise extracted circRNAs in the present study could be utilized in the studies of tissue-specific post-transcriptional regulation involving circRNAs and their role in various buffalo diseases ( Gao et al, 2018 ; He et al, 2021 ; Lei et al, 2021 ; Yang et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%